Sapiosexual as the Intelligence-Oriented Fetish: Is This Just a Popular Term or Does it Need to be Formalized? - Situmorang, Dominikus David Biondi (Bulletin of Counseling and Psychotherapy, 2025)
The author discussed sapiosexuality as a phenomenon that needs to be studied further in the context of sex education. This topic is very current and needs to be discussed more scientifically. The author hopes that through this paper, it can give special consideration to being able to include the discussion of sapiosexuals in the context of formal, informal, and non-formal education. In addition, further researchers are expected to be able to link sapiosexuality with the well-established theory of multiple intelligences. In conclusion, it can be concluded that sapiosexuality is one of the most interesting discussions to be discussed further in the implementation of sexual education in various education sectors, because it is very relevant to the current situation and developments. Despite the controversy and criticism that still occurs in the field, the topic of sapiosexuality will continue to grow stronger by the day. It is evident that currently psychological instruments have been developed to measure this, and there have been quite several scientific studies targeting it. So hopefully, this theory about sapiosexuality can be more scientifically trusted in the future.